FEATURE SHISTORIOSOPHICAL THI - Zalevska, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals on the material "Symphony earth", "Through the centuries" story "Konotop" The influence of history on the specific national artistic thinking Yurij Tys attempt to uncover the deep ties of history of art of the artist to the history of Ukraine.